Satisfaits malgré de bas salaires - Karin Sardadvar; Ekaterina L. Markova; Ambra Poggi (La Nouvelle Revue du Travail)
Jobs characterized by low wages and status should be associated with a low level of job satisfaction. However, this is not always the case. The aim of this chapter is to shed light on the puzzle that emerges in some sectors and occupations where migrants and ethnic minorities experience low-paid and low-status jobs associated with high levels of job satisfaction. Based on qualitative empirical data from the Austrian cleaning, the Bulgarian waste collection and the Italian elderly care sectors, we present four patterns of wage interpretation: (i) ‘Better than nothing’ – the lack of alternatives; (ii) ‘Better than before’ – the heritage of past experiences; (iii) ‘Better than there’ – the comparison with the country of origin; and (iv) ‘Together we get by’ – the wage as a contribution to the family income. We conclude that disadvantaged circumstances and relative interpretations of the wage level lead workers to revise their aspirations downward.